LEGAL PROTECTION FOR COVER SONG CREATORS ON YOUTUBE PLATFORM - Auliah, Nindi; Nadirah , Ida (International Journal of Cultural and Social Science, 2026)
Copyright is regulated in Law Number 28 of 2014 concerning Copyright. Licensing agreements are the main legal instruments that govern the payment of royalties and the inclusion of the creator's name as a way of respecting moral rights. However, in practice, legal protection for songwriters has not been optimal due to low legal awareness among creators, weak law enforcement in the digital space, and ineffective royalty management systems on digital platforms. Therefore, it is necessary to strengthen regulations, raise legal awareness, and optimize the role of governments and digital platforms to create a balance between freedom of expression and copyright protection in the digital economy era